Fractionation of rare-earth elements during magmatic differentiation and weathering of calc-alkaline granites in southern Myanmar. (2nd January 2018) - Sanematsu, Kenzo; Ejima, Terumi; Kon, Yoshiaki; Manaka, Takayuki; Zaw, Khin; Morita, Sayaka; Seo, Yuna
Abstract: Geochemical characteristics and rare-earth element ( REE )-bearing minerals of calc-alkaline granites in southern Myanmar were investigated to identify the minerals controlling fractionation between light and heavy REE (LREE and HREE) during magmatic differentiation and weathering. The granites were classified on the basis of the mineral assemblages into two contrasting groups: allanite-(Ce)- and/or titanite-bearing granites; and more HREE-enriched granites characterized by hydrothermal minerals including synchysite(Y), parisite-(Ce), bastnäsite-(Ce), xenotime-(Y), monazite-(Ce), Y-Ca silicate, waimirite-(Y) and fluorite. This suggests that allanite-(Ce) and titanite are not stable in differentiated magma and HREE are eventually preferentially incorporated into the hydrothermal minerals. The occurrence of the REE -bearing minerals is constrained by the degree of magmatic differentiation and the boundary of two contrasting granite groups is indicated by SiO2 contents of ∼74 wt.% or Rb/Sr ratios of ∼3–8. Fractionation between LREE and HREE during weathering of the granites is influenced by weathering resistance of the REE -bearing minerals, i.e. allanite-(Ce), titanite, the REE fluorocarbonates and waimirite-(Y) are probably more susceptible to weathering, whereas zircon, monazite-(Ce) and xenotime-(Y) are resistant to weathering. Ion-exchangeable REE in weathered granites tend to be depleted in HREE relative to the whole-rock compositions, suggesting that HREE are more strongly adsorbed on weathering products or that HREE remain in residual minerals.